Tissue adhesives: From research to clinical translation - Bal-Ozturk, Ayca; Cecen, Berivan; Avci-Adali, Meltem; Topkaya, Seda Nur; Alarcin, Emine; Yasayan, Gokcen; Li, Yi-Chen Ethan (Elsevier Sci Ltd, 2021)
Sutures, staples, clips, and skin closure strips are used as the gold standard to close wounds after an injury. In spite of being the present standard of care, the utilization of these conventional methods is precarious amid complicated and sensitive surgeries such as vascular anastomosis, ocular surgeries, nerve repair, or due to the high-risk components included. Tissue adhesives function as an interface to connect the surfaces of wound edges and prevent them from separation. They are fluid or semi-fluid mixtures that can be easily used to seal any wound of any morphology-uniform or irregular. As such, they provide alternatives to new and novel platforms for wound closure methods. In this review, we offer a background on the improvement of distinctive tissue adhesives focusing on the chemistry of some of these products that have been a commercial success from the clinical application perspective. This review is aimed to provide a guide to-ward the innovation of tissue bioadhesive materials and their associated biomedical applications. Published by Elsevier Ltd.
Keywords: Sutures; Bioadhesives; Anastomosis; Tissue repair; Wound closure; Injury